Analisis Technology Acceptance Model (TAM) Terhadap Penerimaan Mahasiswa Pada Portal Akademik - Wandira, Raju; Ikwana, Innamul (Insearch: Information System Research Journal, 2021)
The purpose of this study was to evaluate the use of academic information systems among students. Seeing how student admissions use academic information systems for future improvements. This study uses the Technology Acceptance Model (TAM) method which is related to the content design and content quality of academic information systems. Data collection from this study was carried out by using a questionnaire. The questionnaire was filled in by ≥152 respondents consisting of students from various faculties and departments and at different semester levels. By obtaining construct reliability cut off ≥ 0.7 and Average Variance Extracted with cut off ≥ 0.5, the indicator value has good internal consistency. From the results of the analysis conducted, it shows that the significant influence of content quality on content design, quality, and content design on the ease and benefits felt by students. Although there is no significant correlation between ease of use of the portal and its perceived benefits.